PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF PROFESSIONAL (VOCATIONAL) EDUCATION: FOCUS ON EUROPEAN EXPERIENCE (Innovative professional education, 2022)
It is stated that the implementation of reforms for the development of public-private partnership in the field of vocational (vocational) education with a focus on European experience. Mechanisms for the development of public-private partnership in the field of professional (professional and technical) in relation to the labor market are proposed.
Keywords: public-private partnership; professional (vocational) education; European experience